Depression rates among African American inflammatory bowel disease patients at a large safety net hospital. (4th August 2022) - Jordan, Ariel; Mills, Krystal; Sobukonla, Timothy; Bredy, Sancia; Kelly, Alexander; Flood, Michael
Abstract: Aim: Major depressive disorder is a prominent psychiatric illness in the United States. It has been found to be higher among patients with inflammatory bowel disease. However, few studies have focused on depression among minority populations with inflammatory bowel disease. Our study determined the prevalence of depression in minority patients with inflammatory bowel disease at our safety‐net hospital, which serves a predominantly African American patient population. Methods: We conducted a single centre retrospective cohort study at a large, urban outpatient centre. We retrieved the electronic medical records of patients with inflammatory bowel disease who were seen in the gastroenterology clinic from December 2018–December 2019. Data on the severity of depression within the minority population, using the nine‐question Patient Health Questionnaire, was obtained. The effects of age, sex, inflammatory bowel disease diagnosis, and comorbidities were analysed. A p ‐value <0.05 was considered statistically significant. Results: A total of IBD patients were included in the study, of which 46.7% were female and 53.3% were male. Mean age was 44 years. With regard to race, 88.4% were African American, 5.3% Asian, 2.1% Hispanic, 1.1% American Indian/Alaskan Native, and 3.2% multiracial. A total of 71.6% had Crohn's disease and 28.4% had ulcerative colitis. Overall prevalence of major depressive disorder was 25.3%; 45.8% had minimal, 8.3% mild, 33.3% moderate, and 12.5% severe depression. A total of 34.7% of patients were never screened for depression, and 13.8% had other psychiatric conditions. There was a difference in depression rates based on psychiatric conditions ( p = 0.00), but no difference based on sex ( p = 0.37), IBD subtype ( p = 0.34), or medical conditions ( p = 0.84). Conclusions: Rates of depression among minority patients, predominantly African American, with inflammatory bowel disease were higher than previously reported for all patients with inflammatory bowel disease. Over 40% experienced moderate to severe depression. There was a low screening rate for depression. This data will be used to improve depression screening, especially among minorities.